Tools of Iranian policy towards Latin American countries since 2005 - Sarhan Hammadi, Assistant Professor Dr. Dhari (The college of law and political science journal, 2023)
The issue of Iranian policy tools towards Latin American countries is one of thetopics that deserve study and research. Through these tools, Iran has strengthenedLWVSRVLWLRQDQGLQÁXHQFHLQWKLVFRQWLQHQWDQGWKHVWDJHRI3UHVLGHQW0DKPRXGAhmadinejad is one of the most important stages of Iranian policy. It is aimed at it,and it is worth noting that the economic tool was the most successful tool throughwhich the Iranian model became one of the solutions to confront the problemsexperienced by the countries of the Latin continent, in addition to being the toolthrough which they are trying to break the economic sanctions imposed on them.